2023
DOI: 10.3390/rs15123072
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Aerosol Optical Properties over Cluj-Napoca, Romania, Based on 10 Years of AERONET Data and MODIS MAIAC AOD Product

Abstract: Aerosols play an important role in Earth’s climate system, and thus long-time ground- based measurements of aerosol optical properties are useful in understanding this role. Ten years of quality-assured measurements between 2010 and 2020 are used to investigate the aerosol climatology in the Cluj-Napoca area, in North-Western Romania. In this study, we analyze the aerosol optical depth (AOD), single scattering albedo (SSA) and angstrom exponent obtained by the CIMEL sun photometer, part of the aerosol robotic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Aerosol climatology and trends were investigated by Carstea et al (2019) using AERONET observations over continental southeast Europe [35]. Studies investigating the atmosphere over large cities were carried out: Evgenieva et al (2009) studied atmospheric aerosol optical characteristics over Sofia [36]; Stefanie et al (2023) described the temporal variation of aerosol optical properties over Cluj-Napoca [37]; Posyniak et al (2016) examined the long-term variability of aerosol optical thickness over Belsk [38]; Elansky et al (2018) studied air quality and pollutant emissions [39], while Chubarova et al (2016) investigated the temporal variability of the AOD in the Moscow region [40]; and Rupakheti et al (2023) studied aerosol optical properties over Chisinau, Moldova, over two decades [41]. Aerosol-climate interactions were discussed by Markowicz et al (2021), while Filonchyk et al (2021) showed the impact of the COVID-19 lockdown on air quality over Poland [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Aerosol climatology and trends were investigated by Carstea et al (2019) using AERONET observations over continental southeast Europe [35]. Studies investigating the atmosphere over large cities were carried out: Evgenieva et al (2009) studied atmospheric aerosol optical characteristics over Sofia [36]; Stefanie et al (2023) described the temporal variation of aerosol optical properties over Cluj-Napoca [37]; Posyniak et al (2016) examined the long-term variability of aerosol optical thickness over Belsk [38]; Elansky et al (2018) studied air quality and pollutant emissions [39], while Chubarova et al (2016) investigated the temporal variability of the AOD in the Moscow region [40]; and Rupakheti et al (2023) studied aerosol optical properties over Chisinau, Moldova, over two decades [41]. Aerosol-climate interactions were discussed by Markowicz et al (2021), while Filonchyk et al (2021) showed the impact of the COVID-19 lockdown on air quality over Poland [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…This study is a continuation of a series of works devoted to the study of the optical properties of atmospheric aerosol over the Black Sea and its influence on satellite data products presented on the Ocean Color platform. A comprehensive analysis of an array of long-term in situ measurements obtained at AERONET (Aerosol ROboties NETwork) stations (NASA), measurement data from the spectrophotometer SPM (Sun Photometer Mobile) and other independent in situ measurements made it possible to complement the understanding of aerosol load in the region under study and the factors that influence it [1][2][3][4][5][6][7][8][9][10]. In previous studies, background optical characteristics of atmospheric aerosol were obtained for the Black Sea region: aerosol optical depth at a wavelength of 500 nm AOT(500) = 0.22 ± 0.05 and the value of the Ångström parameter (α = 1.3 ± 0.3 [11]).…”
Section: Introductionmentioning
confidence: 99%